Microbiological and Clinical Aspects of Raoultella spp. - Appel, Tobias M.; Quijano-Martínez, Natalia; De La Cadena, Elsa; Mojica, María F.; Villegas, María Virginia (Frontiers in Public Health, 2021)
The genus Raoultella was established in 2001. Species of Raoultella and Klebsiella share many ecological, biochemical, clinical, and microbiological features. Given the shortcomings of available technology for species identification in the clinical microbiology laboratory, are practically indistinguishable. Since the late 2000s there has been an increase in case reports of human Raoultella infections. Therefore, several authors are postulating that Raoultella spp. are rare and/or emerging pathogens. Conclusions:Raoultella spp. are very similar to Klebsiella spp. The epidemiology and the clinical relevance of the human Raoultella spp. infections is uncertain and further studies are required. The previous difficulties in the identification of Raoultella spp. and the introduction of more precise identification techniques may explain the recent increase in the number of case reports. Raoultella spp. might be rather underdiagnosed than rare or emerging pathogens.